Novel subtypes of NPM1-mutated AML with distinct outcome. (4th July 2021) - Mer, Arvind Singh; Minden, Mark D.; Haibe-Kains, Benjamin; Schimmer, Aaron D.
ABSTRACT: Acute myeloid leukemia (AML) is heterogeneous with one common subtype recognized by the presence of recurrent mutation of nucleophosmin-1 ( NPM1 ). Emerging evidence indicates that within NPM1 mutated AML there is variation in outcome which challenges how best to characterize and treat the individual patient. Our recent findings show that there are two distinct (primitive and committed) subtypes within NPM1 mutated AML patients. These subtypes exhibit specific molecular characteristics, disease differentiation states, patient survival, and differential drug responses.